Assessing Writing in French-as-a-Foreign-Language: Teacher Practices and Learner Uptake - Eva Thue Vold (Languages, 2021)
Formative assessment and adaptive instruction have been focus areas in Norwegian educational policy for more than a decade. Writing instruction in the language subjects is no exception; assessment of writing should help the learners improve their writing skills and, thus, feedback must be adapted to the individual learner’s needs. The present study aims to shed light on the relations between teacher feedback practices and learner uptake in French-as-a-foreign-language upper secondary classes in Norway. Using material from a longitudinal corpus of learner texts, including teacher feedback (the TRAWL corpus), the study investigates the written feedback practices of three L3 French teachers, and explores whether any signs of uptake can be identified in 27 learners’ new pieces of writings. The findings show that although the teachers followed best practice principles for formative assessment and written corrective feedback, less than half of the students showed any signs of uptake in subsequent pieces of writing. With one exception, these were students with an intermediate-high to very high proficiency level in French. The study emphasises the importance of strategies that could encourage learners to use the feedback they receive, thus moving the centre of attention from teacher practices to learner activities.